Ideational Intersemiotic Relation in Tempo’s Magazine Cover Representing Setya Novanto - Andriana Vita Nurjannah (Register Journal, 2018)
Magazine cover is an image that accommodates the readers with a critical value information of a news story. The essence of a particular story is able to be represented in a single page of magazine cover. It indeed covers not only the surface or real meanings, but deeper meaning soon to be analysed by the readers. The recent politician case relating Setya Novanto is one of the trending topic in news event as it impacts in the massive reaction from the Indonesian citizens, like making particular memes and even an android game. In this case, the illustrators of one of news magazine, Tempo, have to make a cover representing that event through the visual and verbal composition. Therefore, despite his trial status, this research is aimed at examining the extended meaning depicted from his picture from one national media by identifying visual and verbal elements in the image as the effort to reveal intersemiotic relation between those multimodal modes. This research employed qualitative method, by administering six covers published in 2017 representing Setya Novanto as the news topic. The image and text elements from the cover were identified based on one of metafunctions initially proposed by Halliday (1994), the ideational function. Thus, the intersemiotic analysis were done by relating the visual and verbal meanings (Royce, 1998, 1999, 2002, 2015).Keywords: magazine cover, multimodal, intersemiotic